Predicting Future Events in Poetry - Alghanem, Alanoud Abdulaziz (International Journal of Language and Literary Studies, 2024)
Few research studies on poetical works unintentionally revealed prophetic qualities, in contrast to many novels that have foreseen future events. The goal of this study, therefore, is to investigate two poems as representative examples of prophetic poetry: predictive aspects can be traced in the poem “My Last Duchess” by the Victorian poet Robert Browning, which parallels the story of Diana, Princess of Wales. Similar connections can also be seen between “September 1, 1939” by the modern British-American poet W. H. Auden and the events of the terrorist attack of 11 September 2001. Through textual and contextual analysis, the study utilizes Martin Heidegger’s phenomenological theory of temporality as a means of studying these exemplary poems to demonstrate their resemblance to later events that happened after their publication. The study’s significance lies in its approach of interpreting these poems as predictive works, thereby generating fresh interpretations that question the dominant perspective. The study’s findings will emphasize how poetry can sometimes predict the future, reflecting the recurring nature of historical events and renewing the long relationship between poetry and prophecy.